Changes of coordination modes of Cu-based coordination complexes as tuneable proton-conducting solid electrolytes. Issue 3 (16th December 2016) - Wei, Mei-Jie; Fu, Jia-Qi; Wang, Yi-Di; Gu, Jing-Yang; Liu, Bai-Ling; Zang, Hong-Ying; Zhou, En-Long; Shao, Kui-Zhan; Su, Zhong-Min
Abstract : We have synthesised three proton-conducting coordination complexes as solid proton-conducting electrolytes. Changes of sulfonate group coordination modes and different packing modes, as well as introduction of halide ions may remarkably enhance the proton conductivity of coordination compounds. Abstract : It is essential and vital to develop high-performance proton-conducting solid electrolyte materials for proton exchange membrane fuel cells (PEMFCs), but it remains challenging to design and synthesise such electrolytes with high proton conductivity which are also stable enough to be applied in PEMFCs. Herein, we employed the HCl steam-assisted conversion method to synthesize nonporous coordination complexes with a gradual increase of proton conductivity by stepwise protonation of sulfonated ligands and introduction of halide ions, including [Cu(Hsfpip)(H2 O)2 ]·H2 O (1 ), [CuH2 (Hsfpip)2 (H2 O)] (2 ) and [CuH(Hsfpip)Cl(H2 O)] (3 ) (where Hsfpip is 2-(2, 4-disulfophenyl)imidazo(4, 5- f )(1, 10)-phenanthroline). We reveal the relationship between the nature of proton conduction and structural features. Three resulting coordination complexes showed high proton conductivity with a maximum value of 1.43 mS cm −1 for1, 2.58 mS cm −1 for2 and 15 mS cm −1 for3 at 95 °C and 97% RH, and meanwhile, we proved their proton conduction nature and electron resistance using D2 O-exchange experiments and the Hebb–Wagner polarization method. We believe that these nonporous solid electrolytes intrinsically possess proton carriers and may avoid fuel crossover, which makes them good candidates for PEMFCs in real-life applications.